Potential of therapeutic antioxidant compounds from pomegranate as anti-cancer agent - Mohd Adzim Khalili, Rohin; Nasir, Mohamad; Atif, Amin Baig (2014)
Antioxidants from fruits and vegetables have been extensively studied for their free radical scavenging activities to prevent the occurrence of chronic degenerative diseases. Pomegranate fruit extract possesses antioxidant capacity, superior to many fruits. The fruit extract has been investigated for its anticancer activity on in-vitro cancer cell models, preclinical laboratory animals and early phase clinical trials.The fruit extract has shown more anti-cancer prospect as compared to any of its individual constituents. The pharmacokinetics and mechanism of action of the extract have not been fully established. This may be due to its multiple components that work in tandem to produce its pharmacological activity. This review discusses on some literature that demonstrate the chemotherapeutic potential of pomegranate against some cancers.